2016
DOI: 10.1002/cmr.b.21319
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of and field patterns of surface coils on the electrical properties of the sample and the MR operating frequency

Abstract: In high field MRI, the spatial distribution of the radiofrequency magnetic (B1) field is usually affected by the presence of the sample. For hardware design and to aid interpretation of experimental results, it is important both to anticipate and to accurately simulate the behavior of these fields. Fields generated by a radiofrequency surface coil were simulated using dyadic Green’s functions, or experimentally measured over a range of frequencies inside an object whose electrical properties were varied to ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 47 publications
5
91
0
Order By: Relevance
“…Figure illustrates how the object's dielectric properties influence the |normalB1| field pattern at 64 MHz. This effect is even more pronounced as the operating frequency increases, in which features such as the so‐called dielectric brightening and B 1 twisting are clearly visible, indicating the presence of interference patterns and conduction currents in the sample .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure illustrates how the object's dielectric properties influence the |normalB1| field pattern at 64 MHz. This effect is even more pronounced as the operating frequency increases, in which features such as the so‐called dielectric brightening and B 1 twisting are clearly visible, indicating the presence of interference patterns and conduction currents in the sample .…”
Section: Methodsmentioning
confidence: 97%
“…To motivate the use of tissue‐equivalent phantoms in MRI, we performed full‐wave simulations using an analytic framework based on dyadic Green's functions with objects of various dielectric properties. In particular, we simulated the |normalB1| field of a surface loop coil in the central transverse plane of a head‐sized cylindrical phantom.…”
Section: Methodsmentioning
confidence: 99%
“…Figure c shows the frequency dependence of the B y mode versus the copper connector length. Finally, the effect of the phantom's conductivity on the normalB1+ was examined and is shown in http://onlinelibrary.wiley.com/store/10.1002/mrm.26301/asset/supinfo/mrm26301-sup-0001-suppinfo.pdf?v=1&s=697352a1a323cae037b1da7b64abfeb284bd332d, which shows an asymmetry of the normalB1+ that increases with higher conductivity, in line with work on different coil geometries .…”
Section: Resultsmentioning
confidence: 93%
“…Regarding the mechanism of influence of a pad on the magnetic field in the object, it is known that dielectric and conductive pads behave differently . It has been discussed and demonstrated that according to the modified Ampere’s law, displacement currents in a pad, which are induced by the “primary” B 1 field of the RF coil, act as a secondary source and result in enhancement of the B 1 field in regions of the object proximal to the pad.…”
Section: Resultsmentioning
confidence: 99%
“…where normalσ is the conductivity, εr is relative permittivity, ε0 is free‐space permittivity, normalω is the Larmor frequency, and normalB1+=(B1x+iB1y)/2 is the transmit magnetic field . Equation will be referred to as the standard MREPT (std‐MREPT) method for the reconstruction of EPs.…”
Section: Introductionmentioning
confidence: 99%